Studi literatur: Penerapan Teknologi Artifical Intelligence (AI) Pada Pembelajaran Pendidikan Agama Islam - Hidayatullah Akbar Pratama; Muhammad Ainur Rafiq (MERDEKA : Jurnal Ilmiah Multidisiplin, 2025)
The rapid advancement of digital technology has significantly transformed the educational landscape, including in the domain of Islamic Religious Education (PAI). This study aims to systematically review the application of Artificial Intelligence (AI) in PAI learning through a literature review of scholarly publications from 2020 to 2025. The findings indicate that AI holds great potential in enhancing the quality of learning, particularly in terms of personalization and interactivity (31%), efficiency and teaching innovation (31%), the integration of Islamic values and teacher competency development (23%), as well as providing spiritual support and character formation (15%). However, several major challenges were identified, including limited infrastructure and technology access (30%), the lack of Islamic value verification systems (30%), low digital literacy and teacher readiness (20%), and AI’s current inability to address complex religious matters or detect students' emotional and spiritual aspects (20%). The study concludes that AI integration in PAI must be conducted strategically and adaptively, while upholding spiritual values and enhancing human resource capacity. These findings provide crucial recommendations for educators, technology developers, and policymakers in designing a transformative, relevant, and technology-based Islamic education curriculum.